SOCIALIZATION OF BUSINESS MANAGEMENT AND BRANDING OF COCONUT FIBER PRODUCTS IN SOUTHEAST SULAWESI - Wiwiek Wiyiastuty Soeparyanto; Irelda Sari Syaranamual; Nurafiah Aswawi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service activity aimed to enhance business management understanding and raise awareness of coconut coir–based product branding among coastal MSMEs in Lansilowo Village, Konawe Islands Regency, Southeast Sulawesi. The program was implemented through several stages, including initial observation to identify community needs, socialization activities, educational sessions on basic business management and product branding, and interactive discussions with participants. The results indicate an improvement in participants’ understanding of fundamental business management, such as cost management, simple business planning, and basic financial recording. In addition, participants gained greater awareness of the importance of product branding in increasing product value added, market appeal, and competitiveness of coconut coir–based products. This activity contributes positively to local economic development and the strengthening of coastal MSME capacity, particularly by optimizing the utilization of coconut coir as a value-added economic resource in Lansilowo Village, Konawe Islands Regency.